Community, system and policy level drivers of bovine tuberculosis in smallholder periurban dairy farms in India: a qualitative enquiry - Abhimanyu Singh Chauhan; Mathew Sunil George; Johanna Lindahl; Delia Grace; Manish Kakkar (BMC, 2019)
Abstract Background Rapid urbanization has led to expansion of peri-urban fringes, where intensive, industry-style livestock rearing has led to emerging vulnerabilities at the human-animal-environment interface. This study was undertaken to understand the health system and farm-level factors that influenced the risk of transmission of bovine Tuberculosis (bTB) in animals and humans in peri-urban smallholder dairy farms of India. Methods Thematic guides were developing through literature review and expert consultation. In-depth interviews were conducted till attainment of saturation. Identification of core themes was followed by etiological enquiry and generation of a conceptual model. Results Veterinarians were consulted as a last resort after home-remedies and quacks had failed. Damage control measures, especially with respect to- selling or abandoning sick animals, added to the risk of disease transmission. Although civic authorities believed in the adequacy of a functioning laboratory network, end users were aggrieved at the lack of services. Despite the presence of extension services, knowledge and awareness was limited, promoting risky behaviour. The absence of cogent policies in dealing with bTB was a significant barrier. Stakeholders did not consider bTB to be a major concern. It is possible that they underestimate the problem. Conclusion The current study helps to identify gaps which need to be addressed through collaborative research, and OneHealth interventions to build community awareness.